Deformation and mechanic response of surrounding rock mass during shallow buried large-section tunnel excavation. (November 2019) - Xing, Enda; Lu, Binqiang; Wu, Jimin; Chu, Feifei; Le, Huilin
Abstract: The stability of underground tunnel is closely related to the stress status of surrounding rock mass. Aiming at a typical large-span hydraulic tunnel, the variation of deformation and stress of rock mass during excavation was investigated. Results show that the peripheral convergence of surrounding rock increases with buried depth, and the crown settlement is more sensitive to depth. The horizontal displacement of surrounding rock decreases with the distance to tunnel side wall and the excavation disturbance is about 2 times of the tunnel width. There are obvious time and spatial effects of displacement because of the existence of working face. The restrain distance is about 1.5 times of tunnel width. The excavation of the tunnel changes the stress status of surrounding rock mass. Stress concentration first forms above the crown of the tunnel and then a continuous stress arc develops around the support. The stress arc is favorable to the stability of tunnel.